2021
DOI: 10.1503/jpn.200001
|View full text |Cite
|
Sign up to set email alerts
|

Cortical inhibition, facilitation and plasticity in late-life depression: effects of venlafaxine pharmacotherapy

Abstract: Background: Late-life depression is often associated with non-response or relapse following conventional antidepressant treatment. The pathophysiology of late-life depression likely involves a complex interplay between aging and depression, and may include abnormalities in cortical inhibition and plasticity. However, the extent to which these cortical processes are modifiable by antidepressant pharmacotherapy is unknown. Methods: Sixty-eight patients with late-life depression received 12 weeks of treatment wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
2
3
0
Order By: Relevance
“…Despite prior evidence of interactions between opioid, GABA, and glutamate systems ( 40 ), we did not observe any significant changes in TMS measures of cortical inhibition, facilitation, or plasticity after either BPN or PBO augmentation. Similarly, our previous study of open-label venlafaxine in older adults with MDD did not show an effect of venlafaxine on these cortical measures ( 41 ). Our findings suggest that low-dose augmentation of venlafaxine with BPN does not further engage GABAergic and glutamatergic mechanisms in the cortex.…”
Section: Discussionsupporting
confidence: 59%
“…Despite prior evidence of interactions between opioid, GABA, and glutamate systems ( 40 ), we did not observe any significant changes in TMS measures of cortical inhibition, facilitation, or plasticity after either BPN or PBO augmentation. Similarly, our previous study of open-label venlafaxine in older adults with MDD did not show an effect of venlafaxine on these cortical measures ( 41 ). Our findings suggest that low-dose augmentation of venlafaxine with BPN does not further engage GABAergic and glutamatergic mechanisms in the cortex.…”
Section: Discussionsupporting
confidence: 59%
“…The excitability in prefrontal and motor areas reduced in patients with T2DM and MDD Previous studies have shown that brain excitability of the prefrontal and motor areas in MDD patients reduced compared to healthy subjects, which was related to symptoms like interest drops and reduced activity [31][32][33][34]. similarly, in the present study, we found that patients with T2DM and MDD exhibited lower activation in FPA in comparison with T2DM patients and healthy individuals.…”
Section: Discussionsupporting
confidence: 75%
“…An average signal was obtained from each electrode for each participant. We have reported in detail on these methods in several prior publications including in previous reports on this study [12,25,26,47,51].…”
Section: (G) Electroencephalography Data Processingmentioning
confidence: 99%